Lahirnya Tensi Metafisik di Urat-Leher Projek-Projek Interpretasi Konstruktif - Bakir, Herman; Syamsuddin, Mukhtasar (Jurnal Hukum & Pembangunan, 2025)
This project is a legal hermeneutics. The aim is to elaborate the paradigm of the law as integrity theory, Ronald Dworkin’s work, which has received recognition as one of the most influential philosophical systems in the world of law throughout the last century. The issues discussed are divided into three subjects: (1) the interpretation role in legitimizing “law” as a corpus that has a “soul”; (2) a concept of interpretation from the womb of the law as integrity theory; (3) the dual capacity of “constructive interpretation” in [a] “returning” law to its roots; and [b] housing “morals” within the body of positive law. The result: a kind of final picture for us: (1) The legal text (is a narrative that is) “living”. It is not just bones, flesh, and blood. This is the only component that is never finished in a text. It is always in statu interpretandi—like “a fruit that is never fully ripe.” The reason is its virtus flexibilitatis, which is unmatched by other components—its ability to evolve infinitely, to reincarnate, to adapt in mutatio temporum. At the heart of this pars invisibilis, resides the “soul” that has made every text of legal rules alive, functional, and truly working in its society; (2) Dworkin believes that the soul of every text can only be captured by using constructive interpretation—an interpretive technique that makes the theory of the law as integrity a “great teacher” for it. This theory indoctrinates every judge: the furthest goal of every interpretation is to find the “most sublime point of intersection” between the “three teleological factions”: [a] mens legislatoris; [b] contentio logica and [c] contentio moralis. There, resides the soul of every legal text; (3) This intersection actively drives the internalization and integration of moral values into the legal framework.